The comparison of hislopalhological, immunoperoxidase and immunofluorescence techniques in the diagnosis of rabies in dogs - Sevil (Atalay) Vural (Eurasian Journal of Veterinary Sciences)
In the Study the tissues of 10 rabies suspected dogs obtained from Pendik and Ellik Velennary Control and Animal Diseases Research Institutes were used. The results are as lollows: The nonspecific Inflammatory reactions and degenerative changes delected by histopathologic meihod as regarding rabies were observed in the central nervous system. Gassenan ganglions and parotid glands (10 cases), adrenal glands (7 cases), and submandibular salivary glands (2 cases). The inclusion bodies were seen in the comu ammonis and cerebellum (8 cases), thalamus (3 cases), nucleus caudalus and colliculus rostralis (1 case), also in the Gasserian ganglion (2 cases). In ihe im-munoperoxidase staining meihod. extra and intra celluler rabies virus anligen ancfor the inclusion bodies were seen in central nervous system o/ all dogs and Gassenan ganglion's cell body (9 cases). In addition, ihey were identified in ganglion cell layer ol retina, submandibular salivary gland cells (2 cases), basal cells of cornea, epithelial cells ol parotid gland and duclus, Inlramural ganglion's cell body, kinocilium and nervous libers of trachea, principal cells of stomach, plexus of Intestine and mouth and nose, urinary bladder's epithelium, cells ol hair lollicule of ear and mouth skin, cells of nose mucosa, gland cells ol nose and mouth mucosa (1 case), and kromaffln cells ol adren (6 cases). In the immunofluorescence staining method. Ihe rabies virus anllgen was seen In central norvous system ol all cases, parotid gland cells and lis duel epithelial cells and hair lollicule cells of skin (1 case). Equally positive results were obtained from ihe avidln-biolin peroxidase and indireel immunofluorescence methods which have been used lor the firs! lime in the diagnosis ol rabies in lormalin lixed and parallin embedded tissues in Turkey. Sut the immunoperoxidase method appeared lo be more advaniageous lor use in pathology laboratories since this meihod permitted the usage ol high lllered sera as well as Ihe usage of mora simplified microscopes and the storage of stained slides for a long time.